Combination therapy in chronic periodontitis: a case report - Taherpour, Omid (Novelty in Biomedicine, 2018)
Background: The aim of periodontal treatment is to provide healthy and functional dentition for the whole life. Cases Report: A 42 year old female with sever chronic periodontitis, treated medically and surgically, is reported. She initially received antibiotic, Scaling and root planning in addition to oral hygiene instruction. After four weeks, periodontal Surgery, root canal Therapy, extraction of excess tooth and restoration of some teeth were performed, because of remaining residual pockets, and bone loss, flap Surgery and Access flap, with papilla preservation flap method, also modified Widmann flap, were done. After one month, favorable clinical improvement was obtained. Conclusion: It can be concluded that high oral hygiene level in accompanied with Suitable medical and surgical treatment, enhanced the success of periodontal treatment outcomes even in sever disease.